2022
DOI: 10.3390/molecules27092924
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Reductive Photocatalysis of Azo-Dyes with n–n Junctions Based on Chemically Deposited CdS

Abstract: New composite photocatalysts have been obtained by chemical bath deposition of CdS on top of either nanostructured crystalline ZrO2 or TiO2 films previously deposited on conductive glass FTO. Their morphological, photoelectrochemical and photochemical properties have been investigated and compared. Time resolved spectroscopic, techniques show that in FTO/TiO2/CdS films the radiative recombination of charges, separated by visible illumination of CdS, is faster than in FTO/ZrO2/CdS, evidencing that carrier dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Within the organic chemistry panorama, polymers can guarantee very high versatility in terms of structural and optical response with high potential in several applications [ 78 , 79 , 80 ], but their efficiency is hampered by the low thermal and short-time structural stability of the compounds ( Figure 7 ).…”
Section: Semiconductor Photocatalystsmentioning
confidence: 99%
“…Within the organic chemistry panorama, polymers can guarantee very high versatility in terms of structural and optical response with high potential in several applications [ 78 , 79 , 80 ], but their efficiency is hampered by the low thermal and short-time structural stability of the compounds ( Figure 7 ).…”
Section: Semiconductor Photocatalystsmentioning
confidence: 99%
“…In Table 2 we report the rate values for each CdS/TiO 2 -(1-4) calculated after 30 min of irradiation. The evidence of the photoconversion rate being independent of the concentration of the dye is probably motivated by the fact that the reduction of the azo compound is nearly isoergonic with the occupied electron states in the semiconductor [9,44] and only the highest lying filled electronic states may actually be active in promoting the desired reductive process. We note that the mechanism of this reduction reaction must be complex, since it involves a multielectronic charge transfer possibly accompanied by proton transfer as a charge compensating mechanism.…”
Section: Comparison Of the Composites Cds/tio 2 -(1-4)mentioning
confidence: 99%
“…Fe 2 O 3 [4], Cu 2 O [5] and WO 3 [6] have been used, but cadmium sulfide (CdS) is one of the best, both because of its band gap value (2.4 eV) and appropriate band edge position for photocatalytic redox reactions [7]. Spectral response of CdS/TiO 2 systems can be extended to the visible light region and the appropriate matching of band edges allows the injection of electrons generated from CdS into TiO 2 , effectively increasing the lifetimes of separated charges [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Moreover, some negative aspects typical of CdS itself, such as easy agglomeration and poor photostability, can be improved in the combined photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, the location of the conduction band at negative potentials makes CdS a photocatalyst of interest for reductive transformations that take advantage of electrons promoted in the conduction band [ 23 ]. For example, we recently demonstrated that FTO/TiO 2 /CdS slides, in which CdS was deposited by chemical bath deposition, were an efficient and stable photocatalytic system for the reductive cleavage of N=N bond in azodyes with visible light [ 24 ].…”
Section: Introductionmentioning
confidence: 99%